Reduced sensitivity of the hepatic adenylate cyclase-cyclic AMP system to glucagon during sustained hormonal stimulation. - DeRubertis, F R (1976)
Hormone-induced desensitization of hormonal regulation of cyclic AMP (cAMP) content has been described in a number of tissues. In the present study, we examined responses of rat liver to glucagon after periods of sustained exposure to the hormone in vivo and in vitro. In intact anesthetized rats infused with glucagon (50 ng/min) for 1 h or more and in liver slices incubated with the hormone (10 muM) for this period, hepatic cAMP responsiveness to glucagon was significantly blunted compared with that of tissue exposed to the hormone for shorter periods. The reduction in hepatic cAMP responsiveness to glucagon appeared to be fully expressed by 2 h. With the doses of hormone employed, the sequential alterations in hepatic responsiveness seemed to be limited to the cAMP system, since other parameters of glucagon action did not wane with time. Diminished hepatic cAMP responsiveness during sustained hormonal exposure could not be attributed to decreased glucagon availability, accelerated extracellular release of cAMP, hepatic ATP depletion, or enhanced phosphodiesterase activity. Studies in vitro suggested that modulation of the cAMP response occurred at the level of adenylate cyclase (AC). During sustained exposure of hepatic slices to glucagon, reductions in glucagon-responsive AC correlated temporally with those in cAMP and both changes were reversible. Alterations in glucagon-responsive AC were demonstrated over a wide range of ATP (10 muM-0.1 mM) and glucagon (10 nM-5 MM) concentrations in the cyclase reaction mixture, and appeared to be a noncompetitive phenomenon relative to glucagon. Maximal NaF-responsive AC did not fall concomitantly with time. Thus, the reduction in glucagon-responsive AC was probably not related to a reduction in the catalytic unit of the enzyme, but could have been due to an alteration in glucagon binding to its receptor sites, or in the coupling mechanism involved in transmission of the hormonal signal to the catalytic unit.